Growth and Magnetic characterization of 1D Permalloy Nanowires using self developed AAO Templates. Issue 1 (17th February 2015) - Singh, A K; Khan, G G; Das, B; Mandal, K
Abstract: 1D Permalloy refers to an alloy of Ni and Fe with 80% and 20% composition respectively. 1D Permalloy nanowires are particularly attractive because of their high permeability, low coercivity, near zero magnetostriction and high anisotropic magnetoresistance. Because of low magnetostriction of Permalloy shape anisotropy plays a very important role. As a result, the nanowires show unidirectional anisotropy along their length. Because of this property, they can be used in many applications such as recording head sensors, magnetic storage devices etc. In the present work 1D Permalloy nanowires arrays were fabricated into the pores of self engineered Anodic Aluminium Oxide (AAO) templates by a simple electrodeposition technique (EDT). By varying the Anodization voltage and the parameters of the electrolytic solutions we developed various AAO templates with different average pore diameters. We developed the 1D Permalloy NW's of different diameters depending on the pore size arrangement of AAO templates by varying the deposition conditions. Structural characterization of AAO templates and 1D Permalloy NW's was performed by Transmission and Scanning Electron Microscopy (TEM & SEM). XRD studies of 1D Permalloy NW's shows their fcc crystalline structure and the AAO template was found to be amorphous in nature. Magnetic studies show the 1D Permalloy NW's arrays to have obvious anisotropy, and the easy axis was found to be parallel to the nanowires axis. We performed the angular dependence measurement of 1D Permalloy NW's. When the applied magnetic field was parallel to the nanowires, the coercivity (Hc ) and the maximum remanent ratio (Mr /Ms ) were considerably higher than those while the magnetic field perpendicular to the nanowires. 1D Permalloy NW's developed in this work are expected to be utilize in magnetic memory and magnetic recording devices.